International business English = Tiếng Anh trong kinh doanh quốc tế - Jones, Leo.; Alexander, Richard; Đào Văn Phong (Tp.HCM : Nxb Tp.HCM, 1998)
This is a flexible learner-centred course in communication skills for people who need English in their day-to-day work.The course is suitable for both a broad range of intermediate and more advanced learners.
A course in communication skills.
Keywords: English language; English language -- Business English